Magnetically guided delivery of DHA and Fe ions for enhanced cancer therapy based on pH-responsive degradation of DHA-loaded Fe3O4@C@MIL-100(Fe) nanoparticles. (November 2016) - Wang, Dongdong; Zhou, Jiajia; Chen, Ruhui; Shi, Ruohong; Xia, Guoliang; Zhou, Shu; Liu, Zhenbang; Zhang, NianQing; Wang, Haibao; Guo, Zhen; Chen, Qianwang
Abstract: Dihydroartemisinin (DHA) has been investigated in cancer therapy for its reactive oxygen species (ROS) based cytotoxicity originated from interacting with ferrous ions that may reduce or eliminate the multidrug resistance commonly associated with conventional chemotherapy agents. However, synchronously delivery of hydrophobic DHA and Fe (Ⅲ) ions into tumor cells remains a major challenge. In this work, we develop novel Fe3 O4 @C@MIL-100(Fe) (FCM) nanoparticles for synchronously delivery of DHA and Fe (Ⅲ) for cancer therapy. The MOFs structure based on Fe (Ⅲ) carboxylate materials MIL-100 (Fe) holds great potential for storage/delivery of hydrophobic drug DHA. As a unique nanoplatform, the hybrid inorganic-organic drug delivery vehicles show pH-responsive biodegradation and synchronous releasing of DHA and Fe (Ⅲ) upon reaching tumor sites. The intracellular Fe (Ⅲ) will be reduced further to ferrous ion and interact with DHA to increase its cytotoxicity. The potential of this alternative anti-tumor modality is demonstrated in vivo due to an increased intracellular accumulation of DHA in tumor and activated mechanism via co-release of DHA and Fe (Ⅲ), especially under the guidance of an external applied magnetic field.